Effect of attitude toward work, work environment on the employees’ work self-efficacy - Damianus Abun (Ümit Hacıoğlu, 2021)
The study aimed to determine the influence of the attitude of employees toward work and work environment toward work self-efficacy. To deepen the understanding of the study, literature was reviewed and theories were established. The study used the descriptive correlational research design and it used questionnaires to gather the data. The study found that the cognitive attitude of employees toward work is high but the work environment is at a moderate level. Taking the independent variables together, both are correlated to the work self-efficacy of employees. It means that both, attitude toward work and work environment can affect work self-efficacy. Therefore, the hypothesis of the study is accepted.